Antecedents and Outcomes of Service Recovery Satisfaction: a Study Among Open University Malaysia Students in Klang Valley, Malaysia - Mohd Rushidi Mohd Amin, (2019)
Researchers and practitioners often pay less attention to service recovery research compared to service quality or customer satisfaction particularly in the context of open and distance learning (ODL) in Malaysia. More importantly, the antecedents and outcomes of service recovery satisfaction are often given less emphasis by the ODL institutions in their efforts to gain advantages in the current higher education environment. Based on past literature, four dimensions of justice were used to develop a theoretical understanding of the antecedents of service recovery satisfaction and its outcomes. This study investigated the relationships between justice dimensions (distributive, procedural, interpersonal, and informational), university image, service recovery satisfaction, and customer future outcomes (trust, word of mouth, repurchase intention and loyalty). Data were collected through a survey of 303 OUM students in Klang Valley, Malaysia who experienced service failure and service recovery. This study proposed and tested a framework via Partial Least Square Structural Equation Modeling (PLS-SEM). The results reveal a significant relationship between justice dimensions and service recovery satisfaction in terms of procedural and interpersonal justice. Service recovery satisfaction had a significant effect on all customer outcomes understudy. The inclusion of the university image as moderators were found out does not moderate the relationship between justice dimensions and service recovery satisfaction, implying that the university image does not have a significant interaction effect on this relationship. Therefore, the result of the study will help the managers and professionals to better understand how the antecedents and outcomes of service recovery satisfaction are important for the organisation, and how to deal with the customers in service failure situations to maximise the organisation profit. These results have important implications for marketing theory and business practicality. (Abstract by Author)